HUBUNGAN PENGETAHUAN DENGAN PEMBERIAN MP-ASI PADA BAYI DI BAWAH USIA 6 BULAN DI PUSKESMAS TOSORA - St nurbaya; Indah Indah; Nur Laela; Zainab Zainab (Jurnal Kesehatan Tambusai, 2023)
Many things can be a trigger for parents to give MP-ASI early, one of which is the lack of family knowledge. By seeing the importance of exclusive breastfeeding, the family, especially the husband, must be able to provide full support to assist the mother in providing the best nutrition for the baby. Mothers who breastfeed need emotional support and information from their families so that mothers are more likely to feel confident about their ability to breastfeed or not to give complementary foods early. The study was conducted from March 10 to June 10, 2022. This type of research is an observational method with a cross approach. Sectional Studies. The population in this study was 83. The sample in this study was 45 people. The results showed that the factors related to the provision of early complementary feeding to infants under 6 months in the Tosora Health Center Work Area were the factors of knowledge of the respondents. This is indicated by the p value 0.000 <0.05. There is a significant relationship between the knowledge and attitude variables of the respondents with the early complementary feeding variable where. This is indicated by a p value of 0.000<0.05. Conducting outreach by including material about the dangers of gestational hypertension, how to prevent and treat it so that the public knows about matters relating to the dangers of early complementary feeding in infants under 6 months.